Longevity of Arachis pintoi cv. BRS Mandobi seeds stored under different conditions - Dubbern De Souza, Francisco Humberto; Lessa de Assis, Giselle Mariano; Valentin, Judson Ferreira; Cavariani, Claudio [UNESP] (Abrates-assoc Brasileira Technologia Sementes, 2017)
The goal of this work was to evaluate the storage effects under different temperatures, relative humidities (RH) and packaging types on the seed physiological quality and pod moisture content of Arachis pintoi cv. BRS Mandobi. The fruit of this herbaceous, perennial, leguminous species consists of an indehiscent pod containing a single seed, which is not dehulled for planting purposes. Pod samples presenting an initial 5.8% moisture content and stored under atmospheres presenting 30, 50, 70, 80 and 90% RH at 21 +/- 2 degrees C reached, respectively, the following equilibrium moisture content (EMC): 5.1 +/- 0.3%, 6.2 +/- 0.2%, 7.4 +/- 0.3%, 8.5 +/- 0.2% and 11.6 +/- 0.4%. Pod components (pericarp and seed) differed from one another in terms of EMC when stored under the same RH's; on an average, the pericarp EMC was 4.2% higher than that of the seed. A drastic physiological quality reduction was observed in seeds contained in pods that presented a 6.9% moisture content when storage temperature was raised from 21 +/- 2 degrees C to 30 +/- 3 degrees C. The physiological quality of seeds was preserved for a longer time in semi-permeable packages; this contributed either to maintain low EMC's or to delay reaching higher pod EMC's, depending on the RH under which they were stored.
Keywords: forage peanut; hygroscopic equilibrium; seed packaging; seed quality